Association between bone mineral density and scoliosis: a two-sample mendelian randomization study in european populations - Fangjun Yang; Jiantao Wen (Hereditas)
Abstract Background Previous studies have shown that bone mineral density (BMD) has a certain impact on scoliosis. However, up to now, there is no clear evidence that there is a causal association between the two. The aim of this study is to investigate whether there is a causal association between BMD at different body positions and scoliosis by two-sample Mendelian randomization (MR). Methods Genetic variants (SNPS) strongly associated with BMD (total body BMD (TB-BMD), lumbar spine BMD (LS-BMD), femoral neck BMD (FN-BMD), heel BMD (HE-BMD), and forearm BMD (FA-BMD)) were extracted from GEFOS and genome-wide association analysis (GWAS) databases SNPs) were used as instrumental variables (IVs). Scoliosis was also selected from the Finnish database as the outcome. Inverse variance weighting (IVW) method was used as the main analysis method, and multiple sensitivity analysis was performed by combining weighted median, MR-Egger, MR Multi-effect residuals and outliers. Results IVW results showed that TB-BMD (OR = 0.83, 95%CI: 0.66–1.55 P = 0.13), LS-BMD (OR = 0.72, 95%CI: 0.52–0.99, P = 0.04), FN-BMD (OR = 0.74, 95%CI: 0.50–1.09, P = 0.13), FA-BMD (OR = 0.95,95%CI: 0.70–1.28, P = 0.75), HE-BMD (OR = 0.91, 95%CI: 0.77–1.08, P = 0.29). Sensitivity analyses showed no evidence of pleiotropy or heterogeneity (p > 0.05) (MR-PRESSO and Cochrane). The results were further validated by leave-one-out test and MR-Egger intercept, which confirmed the robustness of the study results. Conclusion In conclusion, the present study demonstrates that the causal role of genetic prediction of scoliosis increases with decreasing lumbar BMD. There was no evidence that BMD at the remaining sites has a significant causal effect on scoliosis. Our results suggest that the lumbar spine BMD should be routinely measured in the population at high risk of scoliosis. If osteoporosis occurs, appropriate treatment should be given to reduce the incidence of scoliosis. Clinical trial number Not applicable